2016
DOI: 10.1007/s00253-016-7483-y
|View full text |Cite
|
Sign up to set email alerts
|

RolB gene-induced production of isoflavonoids in transformed Maackia amurensis cells

Abstract: Maackia amurensis Rupr. et Maxim is a valuable leguminous tree grown in the Russian Far East, in China, and in Korea. Polyphenols from the heartwood of this species (primarily stilbenes and isoflavonoids) possess strong hepatoprotective activity. Callus culture of M. amurensis produced isoflavonoids and their derivatives. In pharmacological experiments, the callus complex was at least as effective, as the plant complex. To increase the yield of isoflavonoids, calli were transformed with the rolB gene of Agroba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…In addition, there is evidence that the fresh and dry weight of rolB lines is significantly lower than that of WT in A. thaliana (Kodahl et al, 2016). It has been documented that the effect of rol genes vary in response among different species (Welander and Zhu, 2010;Grishchenko et al, 2016;Kodahl et al, 2016;Bulgakov et al, 2018). In terms of chlorophyll content, the rolB lines, in the current study, did not differ but had lower content compared to WT, thus not influenced by the differential copy number and expression levels observed.…”
Section: Discussionsupporting
confidence: 44%
“…In addition, there is evidence that the fresh and dry weight of rolB lines is significantly lower than that of WT in A. thaliana (Kodahl et al, 2016). It has been documented that the effect of rol genes vary in response among different species (Welander and Zhu, 2010;Grishchenko et al, 2016;Kodahl et al, 2016;Bulgakov et al, 2018). In terms of chlorophyll content, the rolB lines, in the current study, did not differ but had lower content compared to WT, thus not influenced by the differential copy number and expression levels observed.…”
Section: Discussionsupporting
confidence: 44%
“…Desmodium oxyphyllum (Fabaceae). This plant, also called ticktrefoils, is a medicinal plant from Asia, that is used for breast cancer ( Yoo et al, 2005 ); Maackia amurensis -Rupr (Fabaceae), is a tree also known as Amur maackia ( Yoo et al, 2005 ; Grishchenko et al, 2016 ); Humulus lupulus L. (Cannabaceae) Methanolic plant extracts bind to ERα and ERβ. And it has EA.…”
Section: Other Estrogenic Plantsmentioning
confidence: 99%
“…Such transformed plant cell cultures have been developed in few plant species of Solanaceae, Araliaceae, Rubiaceae, Vitaceae, and Rosaceae families. With few rare exceptions [422], most of the transformed undifferentiated cultures showed enhancement of SMs probably due to the effect of rol gene(s), which is known to be potential activators of SMs as observed in the HRCs [423][424][425][426][427][428][429][430][431][432]. In some cases, the stimulatory effect of individual rol genes was sufficient to overcome the inability of cultured plant cells to produce large amounts of SMs as well as shown to be remarkably stable over long-term cultivation [428].…”
Section: Stable Production Of Sms In Undifferentiated Transformed Culmentioning
confidence: 98%
“…Different rolB-transformed callus lines of Maackia amurensis established by Grishchenko et al [432] showed significant morphological variation such as friable, globular, and yellow whitish to light brown color callus and compact, non-watery, yellow-brown to brown callus, which is correlated with the expression level of rolB gene. Study of the yield of isoflavonoids showed higher amount of isoflavonoid production in rolB-transformed calli (1.4-2.1% DW) compared to 1.22% DW in empty vector control [432]. Similarly, rolC-transformed callus cultures of M. amurensis produced the same complex of isoflavonoids consisting of 20 compounds as the empty vector control and the effect of rolC gene on isoflavonoid production was stable during 4 years.…”
Section: Stable Production Of Sms In Undifferentiated Transformed Culmentioning
confidence: 99%